Different methods of detaching adherent cells and their effects on the cell surface expression of Fas receptor and Fas ligand - Lai, Ting-Yu; Cao, Jerry; Ou-Yang, Pu; Tsai, Ching-Yi; Lin, Chih-Wen; Chen, Chien-Chia; Tsai, Meng-Kun; Lee, Chih-Yuan (Scientific reports, 2022)
In cell culture environment, some cells adhere firmly to the culture plates and may be vulnerable to cell detachment during passage. Therefore, it is important to harvest cells with a proper detaching method to maintain the viability of cells after detachment. Trypsinization is frequently used for cellular dissociation and detachment. However, most surface proteins and the extracellular matrix are degraded by enzymatic digestion. A mild cell detachment buffer, accutase, is recommended for the replacement of trypsin to dissociate adherent cells and thereby avoid cellular damage. In this study, we demonstrated that use of accutase for cellular detachment may compromise some surface proteins. Compared with ethylenediaminetetraacetic acid (EDTA)-based nonenzymatic cell dissociation buffers, accutase was associated with significant decreases in the surface Fas ligands and Fas receptors. Moreover, we found that accutase may be able to cleave surface Fas ligands into pieces. Our results also illustrated that surface proteins required 20 h to recover after accutase treatment. We demonstrated that using accutase to dissociate adherent cells compromised the expression of Fas ligands and Fas receptors on the cell surface. These findings indicate that it is important to choose suitable cell detachment buffers and allow cells to recover after detachment before experiments.